ANALISIS PENINGKATKAN PENDAPATAN PETANI KERAMBA JARING APUNG DENGAN DIVERSIFIKASI SPESIES IKAN BUDIDAYA DI WADUK CIRATA - Gandhy, Abel (Jurnal Ekonomi & Studi Pembangunan, 2017)
TheÂ aim of this research is to analyze the impact of diversification of fish cultivation in floating cage at Cirata Reservoir. Indicators of this study based on Net Present Value (NPV), Internal Rate of Return (IRR), Pay Back Period (PP) and Net B/C. The research showed that diversification activities increases NPV RpÂ 157, 420, 576, raise IRR for 38%, Accelerate the payback period for 3 months and increases the Net B/C from 2.06 to 3,8. Therefore, diversification type of fish cultivation is recommended to apply because will increasing farmer income.